The Handbook of bilingual and multilingual education - Wright, Wayne E.; Boun, Sovicheth; Garcia, Ofelia (Malden, MA Wiley-Blackwell, 2015)
"Represents the first comprehensive reference work that covers bilingual, multilingual, and multicultural educational policies and practices around the world"--Provided by publisher.
1. Introduction: Key Concepts and Issues in Bilingual and Multilingual Education Wayne E. Wright, Sovicheth Boun, and Ofelia Garcâia -- Section 1. Foundations for Bilingual and Multilingual Education 2. Egalitarian Bi/mutilingualism and Trans-semiotizing in a Global World Angel Lin 3. Bilingualism and Creativity: An Educational Perspective Anatoly V. Kharkhurn 4. Language Acquisition in Bilingual Education Guadalupe Valdâes, Luis Poza, and Maneka Deanna Brooks 5. Literacy in Bilingual and Multilingual Education Viv Edwards 6. Culture in Bilingual and Multilingual Education: Conflict, Struggle, and Power Laura A. Valdiviezo and Sonia Nieto 7. A Synthesis of Research on Bilingual and Multilingual Education Colin Baker and Gwyn Lewis 8. Researching Bilingual and Multilingual Education Multilingually: A Linguistic Ethnographic approach Angela Creese [and 8 others] 9. Intersections of Language Ideology, Power, and Identity: Bilingual Education and Indigenous Language Revitalization in French Polynesia Mirose Paia [and 4 others] 10. Language Policy and Planning in Education Terrence G. Wiley 11. Language Rights Tove Skutnabb-Kangas -- Section 2. Pedagogical Issues and Practices in Bilingual and Multilingual Education Practices and Pedagogies for Bilingualism and Multilingualism 12. Programs and Structures in Bilingual and Multilingual Education Nelson Flores and Hugo Baetens Beardsmore 13. Translanguaging, Bilingualism and Bilingual Education Ofela Garâca and Li Wei 14. Multiliteracies, Pedagogies and Academic Literacy Madhav Kafle and Suresh Canagarajah 15. Language Assessment: Past to Present Misuses and Future Possibilities Elana Shohamy and Kate Menken 16. Teacher Education and Support Anne-Marie de Mejâia and Christine Hâelot 17. Parent and Community Involvement in Bilingual and Multilingual Education M. Beatriz Arias School Levels and Special Populations 18. Early Childhood Education and Dual Language Learners Eugene E. Garcâia and Amy M. Markos 19. Primary School Bilingual Education: Pedagogical Issues and Practices Marâia Estela Brisk, Ester J. de Jong, and Meredith C. Moore 20. Secondary Bilingual Education: Cutting the Gordian Knot Christian Faltis and Frank Ramâirez-Marâin 21. Bi/Multilingual Higher Education: Perspectives and Practices Christa van der Walt 22. Bilingual Education and Students with Dis/Abilities and Exceptionalities Teddi Beam-Conroy and Patricia Alvarez McHatton 23. Bilingual Deaf Education Timothy Reagan 24. Bilingual-Multilingual Education and Indigenous Peoples Tiffany S. Lee and Teresa L. McCarty 25. NonFormal Bilingual Education Lesley Bartlett and Monisha Bajaj -- Section 3. Global Dimensions of Bilingual and Multilingual Education 26. A Dual Language Revolution in the United States? On the Bumpy Road from Compensatory to Enrichment Education for Bilingual Children in Texas Deborah K. Palmer, Christian E. Zuänica, and Kathryn Henderson 27. Global Dimensions of Bilingual and Multilingual Education: Canada Thomas Ricento 28. Minority Languages, State Languages and English in European Education Jasone Cenoz and Dukr Gorter 29. Contested Notions of Bilingualism and Trilingualism in the People's Republic of China Anwei Feng and Bob Adamson 30. Bilingual Education in Japan: Slow but Steady Progress Akie Tomozawa and Junko Majima 31. Breaking the Faðcade of Linguistic and Cultural Homogeneity: Education for Multicultural Children in South Korea Jin Sook Lee 32. Striving for Education for All through Bilingual Education in Cambodia Wayne E. Wright and Sovicheth Boun 33. Bilingual and Multilingual Education in Brunei and Malaysia: Policy and Practices Gary M. Jones 34. Multilingual Education in South Asia: The Burden of the Double Divide Minati Panda and Ajit K. Mohany 35. "Too Many Cooks Spoil the Broth": Tension and Conflict Between Language Institutions in South Africa Sinfree Makoni and Busi Makoni 36. A Panoramic View of Bilingual Education in Sub-Saharan Africa: Reorienting the Lens for the Future Leketi Makalela 37. Language Education in Mexico: Access, Equity, and Ideology Peter Sayer and Mario Lâopex Gopar 38. Indigenous Youth and Adult Education in Latin America Luis Enrique Lâopez 39. Multilingual Education across Oceania Joseph Lo Bianco 40. Language, Conflict, and Social Change: Arabic Bilingual Education in the Middle East and North Africa Zeen Zakharia 41. Bilingual and Multilingual Education in the Former Soviet Republics: The Case of Lativa Gatis Dilans and Brigita Zepa.
Includes bibliographical references and index.
Keywords: Multilingualism -- Study and teaching -- Handbooks, manuals, etc; Education, Bilingual -- Handbooks, manuals, etc; Multicultural education -- Handbooks, manuals, etc